Eficácia da terapia a laser de baixa intensidade na redução do edema, dor e parestesia no pós operatório de cirurgias ortognáticas: estudo randomizado duplo cego cruzado - Gasperini, Giovanni (2013)
This study aimed to verify the effectiveness of using a low-level laser therapy protocol to reduce swelling, pain and neurosensory disturbance after orthognathic surgeries. Ten patients who underwent bilateral sagittal split (BSSO) with Le Fort I osteotomy and had low-level laser therapy on one side of the jaw were evaluated over a period of 60 days. The protocol used was intra oral application after surgery (λ = 660 nm (Red), ED = 5J/cm2, t = 10 s / point, P = 20 mW, E = 1.2 J per point). And extra oral application (λ = 789 nm infra-red), DE = 30J/cm2, t = 20 s / point, P = 60 mW, E = 1.2 J per point). After the fourth day, ten intraoral and extraoral applications were performed (λ = 780nm (infrared), DE = 70J/cm2, P = 70 mW, t = 40s / point, E = 2.8 J, per point). Irradiated and non-irradiated side data were compared post-operatively. In all assessments except the immediate post operative assessment, swelling and pain decreased. There is recovery of sensitivity on both sides, but on the irradiated side, recovery is faster and almost normal at the last evaluation. The data for the irradiated and non-irradiated sides were compared post-operatively. Fifteen, 30 and 60 days after surgery, sensitivity was recovered on both sides, but on the irradiated side, recovery was faster and was almost complete at the time of the last evaluation. Irradiated and non-irradiated sides were compared regarding swelling coefficient and Visual Analogue Scale for pain assessment. There were no significant differences between irradiated and non-irradiated sides regarding swelling and pain in the immediate postoperative assessment. Swelling significantly decreased in the irradiated side in the following post-operative assessments, from 2.15 to 0.21 (non irradiated side: 2.72 to 1.29). Self-reported pain was less intense in the irradiated side in the 24-hr (1.20 vs 3.4) and 3-day (0.60 vs 2.10) assessments, but after 7 days of surgery either side did not show any pain. This lower-level laser therapy protocol can improve tissue response and reduce pain and swelling resulting from orthognathic surgeries and accelerate the recovery of neurosensory disorders resulting from BSSO.